2021
DOI: 10.1007/s10584-021-03300-z
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on infectious diseases in the Eastern Mediterranean and the Middle East (EMME)—risks and recommendations

Abstract: The Eastern Mediterranean and Middle East (EMME) region has rapid population growth, large differences in socio-economic levels between developed and developing countries, migration, increased water demand, and ecosystems degradation. The region is experiencing a significant warming trend with longer and warmer summers, increased frequency and severity of heat waves, and a drier climate. While climate change plays an important role in contributing to political instability in the region through displacement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Similarly, climate change can also modify the geographical area, seasonality, survival and growth capacity of several food-and waterborne pathogens, such as Salmonella spp., Escherichia coli, Campylobacter spp. and Legionella spp., as studies have reported in the cities of the Mediterranean Middle East during 2021 [61]. The availability of food can also be affected by crop damage caused by extreme climate events and yield losses especially in maize and wheat.…”
Section: Indirect Effects Environmental Consequencesmentioning
confidence: 97%
“…Similarly, climate change can also modify the geographical area, seasonality, survival and growth capacity of several food-and waterborne pathogens, such as Salmonella spp., Escherichia coli, Campylobacter spp. and Legionella spp., as studies have reported in the cities of the Mediterranean Middle East during 2021 [61]. The availability of food can also be affected by crop damage caused by extreme climate events and yield losses especially in maize and wheat.…”
Section: Indirect Effects Environmental Consequencesmentioning
confidence: 97%
“…The region is faced with the climate change issue, which elevates the likelihood of diseases transmitted through vectors, water, and food. Those facing the highest risk include individuals with lower socio-economic status, limited education, young children, the elderly, migrants, and those dealing with chronic health issues [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this second evaluation process, two papers from RQ1 were excluded. The SLR made it possible to define indicators to be implemented in the framework of use for measuring the probability that this risk might take place [149][150][151][152][153][154]. Political instability is the origin of other possible risks, such as wars, corruption and vandalism, that that can directly strike CH in the form of illegal traffic of assets or destruction in the most extreme cases.…”
Section: Political Instabilitymentioning
confidence: 99%